Banks: Old Actors of the New Economy - Abramova, Marianna G.; Vasilieva, Oxana N.; Yudenkov, Yuri N.; Popova, Anna V.; Milovanova, Marina M.; Safonov, Maxim S. (International Journal of Economics and Financial Issues, 2016)
In the globalization conditions, influence of business both on the states internal life, and on the global system increases. The states are compelled to solve together not only the international problems, but also the tasks, which were mainly internal as long ago as yesterday. An increasing number of the public relations go beyond the national borders, and their regulation is possible only by the states interaction. In this paradigm, the banks, as the central players of the national financial system, can become agents of the new economic policy that seeks to find answers to the new global challenges. It is, above all, the banks role in stimulating the national industry, the possibility of the banks participation in the formation of the new truly competitive economy of the medium and small businesses, directed not on the maximum profit extraction, but first on the public interests satisfaction. In the article, the banks activity change in present period is considered. The banks activity transformation requires the change of the regulation measures, including the states interaction in the globalization conditions. The problems description of the modern Russian banking system in the crisis conditions is given and the possible directions of these problems solution are presented. Keywords: commercial banks, policy, the Bank of Russia, globalization JEL Classifications: E44, E58, E62, F20, F37, F47